A particle swarm optimisation for fuzzy dynamic facility layout problem. (1st January 2011) - Samarghandi, Hamed; Jahantigh, Farzad Firouzi
Dynamic facility layout problem (DFLP) deals with arranging and rearranging the layout plan of a manufacturing system or a service provider throughout several periods. In each period, the material handling costs are different from the previous periods due to the change in the market demand and product mix. Since the problem is NP-hard, numerous approaches have been proposed in the literature in order to find near-optimum solutions of the DFLP. In this paper, we model the natural uncertainty in material handling costs with fuzzy theory. A fuzzy particle swarm optimisation (FPSO) algorithm is proposed to solve the problem. We implement a number of ranking criteria from the literature in order to test the performance of the developed algorithm. Computational results confirm the efficiency and effectiveness of the proposed mechanisms.